Reader Response Criticism: Background, Basic Concepts and Problems - Muhammad Amir Sohail (بازیافت)
The major division of literary theory is presented in a parable, which includes the author, the text and the reader. All critical theories are derived separately from the author, the text and the reader. The only way to understand the text is to understand the author.It ignored the text and the functionality of the reader. Critical theories that relied entirely on the text rejected the author and the reader. Discussions related to Reader response criticism have given rise to new questions. These questions have emerged as issues of reading.This article presents the ideas and concepts in the context of Reader Response criticism, interpretive angles, the importance of reader and the problems of reading. Questions have been raised which will make it possible to look at and understand this critical school of thought from a new angle.